2001
DOI: 10.1038/sj.bjp.0704342
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C involvement in aloe‐emodin‐ and emodin‐induced apoptosis in lung carcinoma cell

Abstract: 1. This study demonstrated aloe-emodin- and emodin-induced apoptosis in lung carcinoma cell lines CH27 (human lung squamous carcinoma cell) and H460 (human lung non-small cell carcinoma cell). Aloe-emodin- and emodin-induced apoptosis was characterized by nuclear morphological changes and DNA fragmentation. 2. During apoptosis, an increase in cytochrome c of cytosolic fraction and activation of caspase-3, identified by the cleavage of its proform, were observed. 3. To elucidate whether the expression of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 37 publications
1
75
0
Order By: Relevance
“…In addition, it was observed that aloe-emodin-induced apoptosis in human hepatocellular carcinoma cell lines HepG2 and Hep3B was accompanied by the induction of p53 and p21 expression (5). Another report suggests that the decrease in the expression of protein kinase Cδ and ε isoforms plays a critical role in aloe-emodin-induced apoptosis (21). A similar role of protein kinase C was observed in U-937 glioma cells (6).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In addition, it was observed that aloe-emodin-induced apoptosis in human hepatocellular carcinoma cell lines HepG2 and Hep3B was accompanied by the induction of p53 and p21 expression (5). Another report suggests that the decrease in the expression of protein kinase Cδ and ε isoforms plays a critical role in aloe-emodin-induced apoptosis (21). A similar role of protein kinase C was observed in U-937 glioma cells (6).…”
Section: Discussionmentioning
confidence: 53%
“…It was reported that, using the human lung squamous carcinoma cell line CH27, apoptosis induced by aloe-emodin was associated with changes in the expression of members of the Bcl-2 family apoptosis regulators (i.e., increase in the Bax level and decrease in Bcl-XL). Aloe-emodin was found to cause cytochrome c release from mitochondria (21). In addition, it was observed that aloe-emodin-induced apoptosis in human hepatocellular carcinoma cell lines HepG2 and Hep3B was accompanied by the induction of p53 and p21 expression (5).…”
Section: Discussionmentioning
confidence: 88%
“…However, several studies indicated that emodin-induced apoptosis was mediated by ROS-generated (Jing et al, 2002;Su et al, 2005) and caspase-and mitochondrial-dependent pathways in human cervical cancer cells (Srinivas et al, 2003). Emodin induced apoptosis in human lung squamous cell carcinoma (Zhang et al, 1999;Lee, 2001), and HepG2/C3A cells were mediated through the activation of p53, p21, Fas/APO-1, and caspase-3 (Shieh et al, 2004). Emodin down-regulates androgen receptor and inhibits prostate cancer cell growth (Cha et al, 2005), and the oxidative injury in lung cancer A549 cells mediated by emodin acts as an early and upstream change in the cell death cascade to antagonize cytoprotective ERK and AKT signaling.…”
mentioning
confidence: 99%
“…[7][8] Although emodin has a high degree of inhibitory activity against various types of tumor cells, the mechanisms of action differ from each other. Some scholars believe that emodin has an apoptosis inducing effect on a variety of tumor cells; its signal transduction pathways for induction of apoptosis mainly include Bax.…”
Section: Discussionmentioning
confidence: 99%